Nitric oxide and exercise: a review - doi: 10.4025/reveducfis.v23i3.11738 - Tácito Pessoa Souza Junior; Ricardo Yukio Asano; Jonato Prestes; Marcelo Magalhães Sales; João Maurício Coelho; Herbert Gustavo Simões (Revista da Educação Física)
Nitric oxide (NO) is a potent vasodilator and hence has a major role in controlling vascular tone. Studies have demonstrated the role of NO in preserving the functional capacity of the endothelium, preventing atherosclerosis, vascular injury, hypertension and others. Moreover, genotype and/or phenotype may reduce the bioavailability of NO resulting in severe endothelial dysfunction, increased peripheral vascular resistance. Recent research has shown that exercise increases the bioavailability of NO in acute and chronic forms. But the production of knowledge related to NO-mediated exercise still has gaps. Thus, the purpose of this brief review is to try elucidate the cellular mechanisms involved in the synthesis and regulation of NO, and demonstrate the advancement of scientific knowledge related to the bioavailability of NO mediated by exercise. For this review were used books and periodicals from the PubMed, HIGWIRE, SciELO and LILACS used “nitric oxide” and “exercise” to search. The main considerations in the study were that exercise increase the acute bioavailability of NO and chronic adaptations of exercise in relation to cardiovascular parameters are dependent on the increased bioavailability of NO induced by exercise.